Non-operative management of perforated peptic ulcer: A single-center experience - Karabulut, Koray; Dincer, Mursit; Liman, Rumeysa Kevser; Usta, Sertac (Turkish Assoc Trauma Emergency Surgery, 2019)
BACKGROUND: Perforation is a rare complication of peptic ulcer. Although the most widely accepted treatment for peptic ulcer perforation is surgery, non-operative treatment can be an option in selected patients. In this study, we aimed to present our non-surgical treatment experience in peptic ulcer perforation. METHODS: In this study, the data of the patients who were treated due to peptic ulcer perforation between January 2012 and September 2017 in our clinic were retrospectively reviewed. The diagnosis was reached by physical examination and radiologic findings. After obtaining the informed consent from the patients, non-operative treatment was performed to the selected patients who had normal vital parameters and did not have findings of generalized peritonitis in the abdominal examination. Oral food and fluid intake were stopped and intravenous fluid, antibiotics and pantoprazole were administered to all patients in this study. RESULTS: A total of 41 patients were treated due to the diagnosis of peptic ulcer perforation in our clinic during the study period. Out of 41 patients, while 35 of the patients were operated, six of them were treated non-operatively. There were peritoneal irritation signs and symptoms in the upper quadrants on physical examination in all of the patients. None of them had generalized peritonitis. Abdominal X-ray and computed tomography were obtained from all of the patients. None of the patients in the non-operative group underwent any interventional procedure or surgery during the follow-up period. The median length of hospital stay was four days in this group. All of the patients were discharged uneventfully. CONCLUSION: Standard treatment of peptic ulcer perforation in most of the patients is still surgical repair. Non-surgical treatment should be kept in mind as an option in the selected patients who had normal vital parameters and did not have any findings of generalized peritonitis in the abdominal examination. In this way, it may be possible to avoid unnecessary surgery and reduce the possible morbidity and mortality associated with the operation.
Peptik ülser perforasyonunun ameliyatsız tedavisi: Tek merkez deneyimi
Keywords: Conservative treatment; non-operative treatment; peptic ulcer perforation